Dynamic transcriptome changes during osteogenic differentiation of bone marrow-derived mesenchymal stem cells isolated from chicken - Lv, Huijiao; Wang, Tao; Zhai, Shangkun; Hou, Zhuocheng; Chen, Sirui (Frontiers in Cell and Developmental Biology, 2022)
Osteoblasts are indispensable for skeletal growth and maintenance. Bone marrow-derived mesenchymal stem cells (BMSCs) are useful in studying osteogenesis. In this study, BMSCs isolated from White Leghorns were differentiated into osteoblasts in vitro. Cells induced for -1, 0, 1, 11, and 22 d were used for transcriptomic analyses using the HISAT2-Stringtie-DESeq2 pipeline. Weighted correlation network analysis was processed to investigate significant modules, including differentially expressed genes (DEGs), correlated with osteogenic differentiation. Gene ontology and pathway enrichment analyses of DEGs were performed to elucidate the mechanisms of osteoblast differentiation. A total of 534, 1144, 1077, and 337 DEGs were identified between cells induced for -1 and 0, 0 and 1, 1 and 11, and 11 and 22 d, respectively (|log2FC| > 1.0, FDR < 0.05). DEGs were mainly enriched in pathways related to cell proliferation in the early stage of osteogenic differentiation and pathways, such as the TGF-β signaling pathway, in the middle and late stages of osteogenic differentiation. A protein–protein interaction network of the 87 DEGs in the MEturquoise module within top 5-%-degree value was built utilizing the STRING database. This study is the first to elucidate the transcriptomic changes in the osteogenic differentiation of BMSCs isolated from White Leghorns at different times. Our results provide insight into the dynamic transcriptome changes during BMSC differentiation into osteoblasts in chicken.